Empowering Vocational Graduates: How Educational Resource Innovation Drives Competitiveness Through Digital Skills - Tunul Lasniatin; Mohammad Syadeli Hanafi; Asep Muhyidin; Budi Ilham Maliki; Alifia Hanifah Mumtaz (Berkala Ilmiah Pendidikan, 2026)
This study aims to analyze the effect of educational resource innovation on the competitiveness of vocational high school (SMK) graduates in Serang City through digital competence as a mediating variable. The research is motivated by the high unemployment rate among SMK graduates, despite the region's dominance of vocational education institutions. This study employed a quantitative, explanatory research design. The population consisted of unemployed SMK graduates in Serang City, with a sample of 300 respondents selected using proportional random sampling. Data were collected through a Likert-scale questionnaire that had been tested for validity and reliability. Data analysis was conducted using Structural Equation Modeling (SEM) with LISREL to examine direct and indirect relationships among variables. The results indicate that educational resource innovation has a significant positive effect on digital competence and graduate competitiveness Digital competence significantly influences graduate competitiveness and partially mediates the relationship between educational resource innovation and competitiveness. These findings suggest that innovative, collaborative, and digitally integrated educational resource management is a strategic factor in enhancing the competitiveness of vocational graduates in the digital era.